Review of the most applicable regulator collections to control the Parallel Active Power Filter - Belkacem Gasmi; Othmane Abdelkhalak (Institute of Advanced Engineering and Science, 2018)
This work presents a study of the three-phase parallel active power filter and the various controllers used in its control. Moreover, in order to improve the quality of electrical energy, by making it conform to the new normative constraints, we have also been led to develop and apply advanced automation methods. In this framework, this paper reports of several regulatory structures : fuzzy logic, PWM, new space vector PWM (NSVPWM), space vector PWM (SVPWM), HYSTERESIS moreover, in order to produce a parallel active filter, a thorough study of experimental feasibility was carried out, taking into account the industrial constraints of the product both in its design and its application.